Planning ahead in public health? A qualitative study of the time horizons used in public health decision-making - Taylor-Robinson, David C (BioMed Central, 2008)
BACKGROUND: In order to better understand factors that influence decisions for public health, we undertook a qualitative study to explore issues relating to the time horizons used in decision-making. METHODS: Qualitative study using semi-structured interviews. 33 individuals involved in the decision making process around coronary heart disease were purposively sampled from the UK National Health Service (national, regional and local levels), academia and voluntary organizations. Analysis was based on the framework method using N-VIVO software. Interviews were transcribed, coded and emergent themes identified. RESULTS: Many participants suggested that the timescales for public health decision-making are too short. Commissioners and some practitioners working at the national level particularly felt constrained in terms of planning for the long-term. Furthermore respondents felt that longer term planning was needed to address the wider determinants of health and to achieve societal level changes. Three prominent 'systems' issues were identified as important drivers of short term thinking: the need to demonstrate impact within the 4 year political cycle; the requirement to 'balance the books' within the annual commissioning cycle and the disruption caused by frequent re-organisations within the health service. In addition respondents suggested that the tools and evidence base for longer term planning were not well established. CONCLUSION: Many public health decision and policy makers feel that the timescales for decision-making are too short. Substantial systemic barriers to longer-term planning exist. Policy makers need to look beyond short-term targets and budget cycles to secure investment for long-term improvement in public health.